2005
DOI: 10.1007/bf03245920
|View full text |Cite
|
Sign up to set email alerts
|

GPCRs as therapeutic targets: a view on adenosine receptors structure and functions, and molecular modeling support

Abstract: G-protein-coupled receptors (GPCRs) represent the largest known family of signal-transducing proteins and transmit signals for light and many extracellular regulatory molecules. GPCRs are dysfunctional or dysregulated in several human diseases and are estimated to be the targets of ~40% of the drugs used in clinical medicine today. Receptors for adenosine belong to this family, and so far four subtypes, the A 1 , A 2A , A 2B , and A 3 , have been recognized. The activation of adenosine receptors (ARs) is large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 59 publications
(71 reference statements)
0
3
0
Order By: Relevance
“…The endonucleoside adenosine modulates a wide range of physiological and pathological processes through the activation of adenosine receptors, which belong to a superfamily of G-protein-coupled receptors (GPCR) and can be subdivided into four subtypes A 2A , A 2B , A 1 , and A 3 . The A 2A adenosine receptor (A 2A AR) increases adenylate cyclase activity and levels of intracellular second messenger 3′,5′-cyclic adenosine monophosphate (cAMP), which triggers a series of cellular events .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The endonucleoside adenosine modulates a wide range of physiological and pathological processes through the activation of adenosine receptors, which belong to a superfamily of G-protein-coupled receptors (GPCR) and can be subdivided into four subtypes A 2A , A 2B , A 1 , and A 3 . The A 2A adenosine receptor (A 2A AR) increases adenylate cyclase activity and levels of intracellular second messenger 3′,5′-cyclic adenosine monophosphate (cAMP), which triggers a series of cellular events .…”
Section: Introductionmentioning
confidence: 99%
“…The endonucleoside adenosine modulates a wide range of physiological and pathological processes through the activation of adenosine receptors, which belong to a superfamily of Gprotein-coupled receptors (GPCR) 1 and can be subdivided into four subtypes A 2A , A 2B , A 1 , and A 3 . 2 The A 2A adenosine receptor (A 2A AR) increases adenylate cyclase activity and levels of intracellular second messenger 3′,5′-cyclic adenosine monophosphate (cAMP), 3 which triggers a series of cellular events. 4 In the human body, the A 2A AR is ubiquitous and expressed in a variety of organs and tissues, such as the heart, lung, liver, neutrophil, leukocyte, and endothelial cells, implying its role in the regulation of inflammatory and immune responses.…”
Section: Introductionmentioning
confidence: 99%
“…Ado a is involved in the regulation of many physiological and pathophysiological processes through the activation of four cell membrane receptors, termed A 1 , A 2A , A 2B , and A 3 , which belong to the family of G-protein coupled receptors and are ubiquitously expressed in the body. In particular, the A 3 receptor is negatively coupled to adenylyl cyclase and positively coupled to phospholipase C, resulting in an increase of intracellular Ca ++ levels. , Although the physiological role of the A 3 receptor subtype is not fully understood yet, it has recently attracted considerable interest as a novel drug target . In particular, it has been suggested that A 3 receptor agonists may have potential as cardioprotective , and cerebroprotective agents.…”
Section: Introductionmentioning
confidence: 99%